Recent Apareiodon species evolutionary divergence (Characiformes: Parodontidae) evidenced by chromosomal and molecular inference - Traldi, Josiane Baccarin (2020)
This paper presents results from a comparative analysis of cytogenetic markers, DNA barcode, molecular delimitation and population genetics among four groups of Apareiodon samples inhabiting four headwater streams feeding the Tocantins River in Brazil's Tocantins River Basin. Apareiodon is a genus of Parodontidae, a Neotropical fish family whose members show often-subtle morphological diagnostic characters that complicate identification of its constituent species. The samples were previously morphologically identified as Apareiodon machrisi, Apareiodon cavalcante, Apareiodon sp. 1, and Apareiodon sp. 2. The cytogenetic results showed a shared diploid number of 54 chromosomes, and no heteromorphic sex chromosomes were detected. In situ localization of repetitive DNA sequences (18S and 5S ribosomal DNAs, (GATA)(n) sequence, pPh2004 satellite DNA, and WAp repetitive fraction) revealed karyotype differences among the four groups of samples. The K2P genetic distance among the groups ranged from 0.79 to 4.27%. Species delimitation analyses diverge in taxa number: general mixed Yulecoalescent data suggested the occurrence of three species; and the Bayesian and neighbor-joining trees revealed four clades, three of them being supported clades (A. machrisi thorn Apareiodon sp. 1, A. cavalcante, and Apareiodon sp. 2). Haplotypes did not overlap and high Fst values were observed among the groups. The data suggest that these samples have had a recent parapatric divergence: A. cavalcante and A. machrisi are valid species; Apareiodon sp. 1 may be a lineage related to A. machrisi, possibly undergoing an incipient process of speciation; and Apareiodon sp. 2 may be a new Apareiodon molecular operational taxonomic unit. (c) 2020 Elsevier GmbH. All rights reserved.